IN SITU ATOMIC FORCE MICROSCOPE OBSERVATIONS OF A DISSOLUTION-CRYSTALLISATION REACTION: THE PHOSGENITE-CERUSSITE TRANSFORMATION - THEORY, EXPERIMENT, AND APPLICATIONS - Pina C.M.; Fernandez-Daz L.; Prieto M.; Putnis A. (My University, 2000)
The dissolution-reprecipitation reaction of phosgenite (Pb2Cl2CO3) to cerussite (PbCO3) has been observed in situ in a fluid cell of an atomic force microscope (AFM). The (001) face of phosgenite, in contact with static carbonated aqueous solutions, rapidly begins to dissolve. AFM observations show that dissolution occurs by generation and spread of square-shaped etch pits with sides parallel to <110> directions. The dissolution of the <110> steps is isotropic and the etch pits therefore remain square shaped during the dissolution process, as dictated by the existence of a fourfold axis perpendicular to the phosgenite (001) face. Two types of <110> etch pits were found: short-lived shallow pits, of one unit cell depth (8.8 #9), and deep pits, which rapidly reach depths between 10 and 60 nm. A few minutes after the dissolution begins, only the deep pits remain and subsequent dissolution of the phosgenite (001) surface proceeds by increasing their width and depth. The increase of Pb2+ and CO32- concentration in the aqueous solution as a consequence of the dissolution sharply increases the supersaturation for PbCO3. As a result, after a certain incubation time, cerussite crystals nucleate on the phosgenite (001) surface and a coupled process of dissolution-crystallisation starts. Cerussite crystals, which grow by a spiral-growth mechanism, distort the concentration field around them. As a consequence, phosgenite dissolution is accelerated in the proximity of such growing cerussite individuals and both the formation of new deep etch pits and the development of irregular dissolution fronts are observed. Further phosgenite dissolution leads to an increase of cerussite nucleation and growth rates, in such a way that this dissolution-crystallisation phenomenon can be considered as an autocatalytic process.